Influence of functional condition of visual sensory system on motive preparedness of school-age children - Azhippo, A. Ye; Shesterova, L. Ye.; Maslyak, I. P.; Kuzmenko, I. A.; Bala, T. M.; Krivoruchko, N. V.; Mameshina, M. A.; Sannikova, M. V. (My University, 2017)
Purpose: to define the extent of influence of specially oriented exercises on functional condition of visual analyzer and the level of physical fitness of pupils of 7-15 years old. Material: the researches were conducted on the basis of comprehensive educational institutions of Kharkov, more than 800 pupils, of whom 6 experimental and 6 control groups were made, took part in them. Results: the level of motive preparedness of pupils is determined; the functional condition of visual sensory system is investigated; distinctions of the studied indicators in age and gender aspects are considered; the interrelation between parameters of functional condition of visual sensory system and the level of development of motor abilities of pupil is defined; the extent of influence of specially oriented exercises on functional condition of the visual analyzer and motive preparedness of examinees is revealed. Conclusions: 1. Data of initial researches allowed to establish that borders of achromatic (colorless) field of vision of pupils of 7-15 years old are fewer norms. 2. The correlation analysis showed the existence of rather close interrelation between visual analyzer and level of development of physical qualities. 3. Application of specially selected exercises positively influenced functioning of visual analyzer and indirectly on motive preparedness of examinees.
Influence of functional condition of visual sensory system on motive preparedness of school-age children / A. Ye. Azhippo, L. Ye. Shesterova, I. P. Maslyak, I. A. Kuzmenko, T. M. Bala, N. V. Krivoruchko, M. A. Mameshina, M. V. Sannikova // Journal of Physical Education and Sport. – 2017. – № 04. – Р. 2519–2525.
Keywords: physical education, children of school age, visual sensory system, motor abilities; физическое воспитание, дети школьного возраста, зрительная сенсорная система, двигательные способности; фізичне виховання, діти шкільного віку, зорова сенсорна система, рухові здібності